Pilot Fatigue—A Study on the Effectiveness of Flight and Duty Time Regulations for Professional Pilots in Canada - David-Cooper, René (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2019)
In Canada, federal regulations govern the maximum time a professional pilot may fly an aircraft (flight time) and be on duty at his or her workplace (duty time). This report summarizes the findings of a study conducted in 2016-2017, which analyzed the effectiveness of flight and duty time (FDT) regulations for professional pilots in Canada. More specifically, this study was conducted to assess whether the current FDT regime adequately protects the safety of air crews and passengers onboard Canadian aircraft. This study focuses on Canadian operators conducting commercial operations under Part VII of the Canadian Aviation Regulations (CARs) as aerial work, air taxi, and commuter and airline operators. It analyzes whether federal laws adequately regulate pilot fatigue and whether there are any gaps within the CARs. Because the CARs regulate FDT differently depending on the category of operator, this study also considered potential safety trends with respect to pilot fatigue in various categories of carriers; the effects of standby duty; the risks associated with being awake for extended periods of time; and whether less experienced pilots are more vulnerable to pilot fatigue in comparison to more experienced pilots. Five key informants, who worked as professional pilots in Canada, were interviewed in the course of this study to substantiate certain hypotheses. Following these interviews, this report was produced. It focuses on five aspects of FDT regulations in order to understand their positive or adverse impact on pilot fatigue: (1) work schedules; (2) pilot remuneration; (3) fatigue and stress; (4) company safety culture and work environment; and (5) industry issues.